Airline Travelers' Causal Attribution of Service Failure and Its Impact on Trust and Loyalty Formation: The Moderating Role of Corporate Social Responsibility. Issue 4 (2nd April 2016) - Nikbin, Davoud; Hyun, Sunghyup Sean; Iranmanesh, Mohammad; Maghsoudi, Amin; Jeong, Chul
Abstract : This study examines airline travelers' causal attribution (stability and controllability) and its impact on trust and loyalty formation and investigates the moderating role of corporate social responsibility (CSR) in this process. Based on a literature review, theoretical relationships between stability, controllability, CSR, trust, and loyalty were derived, and the moderating effects of CSR on relationships between stability/controllability and trust/loyalty were examined. To empirically test these theoretical relationships, quantitative data were collected from 271 airline passengers who experienced a service failure in the past year. The results provide support for effects of stability and controllability on trust as well as the effect of stability on loyalty. In addition, the perception of CSR had positive effects on trust and loyalty. Finally, a favorable CSR perception weakened the negative effects of a service failure on trust and loyalty, particularly when the failure was attributed to a stable cause. The results highlight the important role of CSR in service failure situations and have important implications for airline managers.